OPTIMIZATION OF GEOMETRY AND BUILDING ORIENTATION ON THE ACCURACY OF DISSOLVING MICRONEEDLE MASTERS USING STEREOLITHOGRAPHY - Sianipar, Christoforus; Erline, Indriani; Sari, Wangi (Journal of Applied Engineering Science, 2025)
Microneedles have gained prominence as a minimally invasive transdermal drug delivery technology, offering significant advantages such as reduced pain, targeted drug delivery, and decreased medical waste. This study focuses on the optimization of dissolvable self-locking microneedles fabricated using stereolithography (SLA), with an emphasis on dimensional accuracy. Three microneedle geometries—perpendicular, concave, and convex—were investigated across three building orientations (0°, 45°, and 60°). Microneedle masters were printed using SLA and subsequently used as molds to fabricate PDMS microneedle molds. Dimensional accuracy was evaluated based on errors in height, base, and angle, with optimization conducted using the Taguchi method. The results revealed that for microneedle masters, the perpendicular geometry paired with a 45° building orientation demonstrated the best accuracy, as confirmed by S/N ratio analysis and ANOVA. For microneedle molds, perpendicular geometry remained optimal, with the 60° orientation offering reduced errors due to improved stability during the demolding process. Morphological comparisons indicated notable differences between master and mold accuracy, attributed to stresses during demolding. This study underscores the critical role of geometry and building orientation in optimizing microneedle fabrication and highlights the effectiveness of the Taguchi method in reducing dimensional errors.